Combined effects of HIV and obesity on the gastrointestinal microbiome of young men who have sex with men. Issue 6 (27th December 2019) - Cook, RR; Fulcher, JA; Tobin, NH; Li, F; Lee, D; Woodward, C; Javanbakht, M; Brookmeyer, R; Shoptaw, S; Bolan, R; Aldrovandi, GM; Gorbach, PM
Abstract : Objectives: The prevalence of obesity is rising among people living with HIV, which may synergistically increase inflammation and the risk of associated diseases. Disruption of gut bacterial communities may be one of the key drivers of this inflammation; however, the combined effects of HIV and obesity on the microbiome have not been explored. Methods: This study included 381 men who have sex with men. Thirty‐nine were HIV‐positive and obese (H+O+), 143 were HIV‐positive and nonobese, 64 were HIV‐negative and obese, and 135 were HIV‐negative and nonobese. Microbiome composition was assessed by targeted sequencing of the V4 region of the 16S ribosomal RNA (rRNA) gene using rectal swab samples. Inverse probability of treatment‐weighted marginal structural models were used to investigate differences in microbial composition between groups while controlling for numerous clinical and behavioural confounders. Results: Significant variability in microbial composition was explained by the combination of HIV and obesity, over and above each condition alone ( R 2 for the marginal contribution of the H+/O+ group = 0.008; P = 0.001). H+O+ participants had the highest ratios of Prevotella to Bacteroides, a pro‐inflammatory enterotype that has been described in HIV infection and obesity independently. H+O+ participants had lower levels of Bacteroides and Veillonella than all other groups, suggesting a synergistic effect of HIV and obesity on these genera. Conclusions: Our findings support the hypothesis that HIV and obesity act together to disrupt gut microbial communities, which may help explain higher levels of generalized inflammation among people living with both HIV and obesity.